Effects of Compulsory Schooling on Mortality – Evidence from Sweden - Martin Fischer; Martin Karlsson; Therese Nilsson (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Theoretically, there are several reasons to expect education to have a positive effect on health, and empirical research suggests that education can be an important health determinant. However, it has not yet been established whether education and health are indeed causally-related, and the effects found in previous studies may be partially attributable to methodological weaknesses. Moreover, existing evidence on the education-health relationship using information of schooling reforms for identication, generally uses information from fairly recent reforms implying that health outcomes are observed only over a limited time period. This paper examines the effect of education on mortality using information on a national roll-out of a reform leading to one extra year of compulsory schooling in Sweden. In 1936, the national government made a seventh school year compulsory; however, the implementation was decided at the school district level, and the reform was implemented over a period of 12 years. Taking advantage of the variation in the timing of the implementation across school districts,by using county-level proportions of reformed districts, census data and administrative mortality data, we find that the extra compulsory school year reduced mortality. In fact, the mortality reduction is discernible already before the age of 30 and then grows in magnitude until the age of 55-60. – – In der Theorie existieren verschiedene Erklärungen, warum Bildung Gesundheit positiv beeinflussen sollte, und ein Zusammenhang zwischen beiden wird mittlerweile als empirisch gesichert angesehen. Ob es sich dabei allerdings um eine kausale Beziehung handelt, ist weiterhin umstritten. Studien, die Schulreformen als exogene Variation in der Ausbildungsdauer nutzen um kausale Zusammenhänge zu identifizieren, beziehen sich dabei mehrheitlich auf Änderungen im Schulwesen während der zweiten Hälfte des 20. Jahrhunderts. Damit sind Aspekte der Gesundheit, insbesondere die Sterblichkeit, nur über einen begrenzten Zeitraum beobachtbar. In der vorliegenden Studie werden die Auswirkungen einer Ausdehnung der Schulpflicht um ein Jahr auf Sterblichkeitsraten in Schweden untersucht. 1936 beschloss die schwedische Regierung, das siebte Schuljahr verpflichtend zu machen. Die exakte Einführung des zusätzlichen verpflichtenden Schuljahres oblag allerdings den jeweiligen Schuldistrikten und erstreckte sich über einen Zeitraum von 12 Jahren. Durch Ausnutzung der zeitlichen Variation auf Schuldistriktebene kann eine Reduktion der Mortalität durch eine Ausweitung der Schulpflicht beobachtet werden. Dabei sind Effekte bereits vor dem Erreichen des 30. Lebensjahres beobachtbar und nehmen an Effektgröße bis zum Alter von 55-60 Jahren weiter zu.
Keywords: I12; I14; I18; I21; 330; returns to schooling; education reform; mortality